An electrochemical comparison of thiolated self‐assembled monolayer (SAM) formation and stability in solution on macro‐ and nanoelectrodes. Issue 6 (9th December 2021) - Piper, Andrew; Corrigan, Damion K.; Mount, Andrew R.
Abstract: Thiolated self‐assembled monolayers (SAMs) formed on metal electrodes have been a topic of interest for many decades. One of the most common applications is in the field of biosensors, where this is a growing need for functionalizing nanoelectrodes to realize more sensitive and implantable sensors. For all these applications, the SAM‐functionalized nanoelectrodes will need to make reliable and interpretable electrochemical measurements. In this work, electrochemical impedance spectroscopy (EIS) is used to monitor both the formation and subsequent stability of 6‐mercaptohexan‐1‐ol SAMs on macro and nanoelectrodes and compares the two. To develop effective devices, it is crucial to understand both SAM formation and the resulting signal stability on nanoscale surfaces and this is done by comparing to behaviors observed at the well‐understood macroscale. We report an initial stochastic binding event and subsequent re‐arrangement of the SAMs for both electrode types. However, this re‐arrangement takes hours on the macroscale electrodes but only seconds on the nanoelectrodes. This is proposed to be due to the different structures of the SAMs on the electrodes predominantly driven by their bulk‐to‐edge ratios. After formation, the SAMs formed on both macro‐ and nanoelectrodes exhibit significant instability over time. The reported results have practical implications for the construction of SAM‐based biosensors on macro‐ and nanoscale electrodes.